Parotid sialolithiasis with Stenson’s duct stricture: a rare case report - Raza, Mohammed; Gupta, Mohit (International Surgery Journal, 2020)
Sialolithiasis is the most common disease that affects the major salivary glands and occurs mainly in the submandibular gland (80-90%), and to a lesser degree in the parotid gland (5-20%). In literature many papers have been published regarding the parotid calculi and their treatment. However, data on salivary duct strictures management is less with variable opinion. We present a case of 45-year-old female with swelling of right parotid for 6 months, USG showed duct calculi with sialadenitis and sialogram showed large duct calculi with high grade strictures. Duct calculi was removed by intra-oral approach and parotidectomy was done as endoscopic management of strictures failed. This was highlighted case as parotid duct calculi along with high grade strictures are rare.